Book of Dreams : Brussels artists decolonizing the city - Wilson, Dorrie A.; Wallyn, Jan; Leboutte, Audrey (Brussel : Zinnema, 2017)
Botan, Muhiba ; Nsengiyumva, Laura ; Vandebergh, Oriane ; Heremans, Sandra ; projectwww ; Aduhire, Yves ; Ntela, Hendrickx ; Mangoo Pickle
boek